2020
DOI: 10.1037/sah0000171
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety sensitivity and acculturative stress facets among Latinx in primary care.

Abstract: The present investigation examined associations between anxiety sensitivity and acculturative stress, both as a global construct and in relation to each of its facets. We hypothesized that anxiety sensitivity would significantly predict acculturative stress (and its facets), over and above the variance accounted for by gender, age, marital status, years of education, employment status, number of years living in United States, and negative affectivity. Participants (N ϭ 142; M ϭ 39.1 years, SD ϭ 12.4; 96% repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 47 publications
1
5
0
Order By: Relevance
“…Results from both samples provide evidence that AS is significantly positively associated with COVID-related worry, anxiety, functional impairment and symptoms severity, and these associations were evident over and above the variance accounted for by age, sex, pre-existing medical conditions, and possible COVID-19 exposure. These results are in line with past work among Latinx adults documenting associations between AS and mental health outcomes (e.g., Viana et al 2020 ; Zvolensky et al 2020d ), and extends the findings to COVID-19 specific mental health and functional outcomes. Additionally, the finding that AS is related to more severe COVID-19 symptoms independent of COVID-19 exposure is particularly clinically important, as AS has been shown to be associated with increased risk of chronic medical conditions (Horenstein et al 2018 ; Lipsitz et al 2004 ), and may worsen COVID-19 outcomes for those with the virus.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Results from both samples provide evidence that AS is significantly positively associated with COVID-related worry, anxiety, functional impairment and symptoms severity, and these associations were evident over and above the variance accounted for by age, sex, pre-existing medical conditions, and possible COVID-19 exposure. These results are in line with past work among Latinx adults documenting associations between AS and mental health outcomes (e.g., Viana et al 2020 ; Zvolensky et al 2020d ), and extends the findings to COVID-19 specific mental health and functional outcomes. Additionally, the finding that AS is related to more severe COVID-19 symptoms independent of COVID-19 exposure is particularly clinically important, as AS has been shown to be associated with increased risk of chronic medical conditions (Horenstein et al 2018 ; Lipsitz et al 2004 ), and may worsen COVID-19 outcomes for those with the virus.…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, since AS amplifies the affective response to somatic perturbation (Drahovzal et al 2006 ; Varela et al 2007 ), AS may be particularly important to the Latinx population. Consistent with this formulation, non-COVID-19 related research has found that AS is associated with greater anxiety (Zvolensky et al 2018b ), depression (Zvolensky et al 2020b ), stress (Viana et al 2020 ), posttraumatic stress (Zvolensky et al 2020d ), pain (Bakhshaie et al 2019 ; Kauffman et al 2019 ), and substance use problems (Zvolensky et al 2020a ) among Latinx adults. Work among trauma-exposed Latinx samples, which is likely relevant to the current COVID-19 pandemic, suggests that AS is associated both with elevated mental health complaints as well as acculturative stress (Zvolensky et al 2018a ).…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…Of the 32 articles, 23 referred to the participants as “Latino” (Bakhshaie et al, 2018; Castillo et al, 2015; Corona et al, 2017; Ertl et al, 2018; Gutierrez-Vazquez et al, 2018; Hill et al, 2019; Leong et al, 2013; Maldonado et al, 2018; Mayorga et al, 2018; Panchang et al, 2016; Paulus et al, 2019; Ramos et al, 2015; Rivera et al, 2015; Rogers-Sirin, 2013; Salgado et al, 2012; Sanchez et al, 2016; Savage & Mezuk, 2014; Schachter et al, 2012; Torres et al, 2012; Viana et al, 2020; Waldman et al, 2019; Zvolensky et al, 2018, 2020). There were two studies that referred to the sample population as “Hispanic” (Cervantes et al, 2013; Zvolensky et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Of the reviewed articles, 81.2% investigated the interaction of acculturative stress on mental health (Bakhshaie et al, 2018; Capielo et al, 2015; Castillo et al, 2015; Cervantes et al, 2013, 2019; Corona et al, 2017; Gutierrez-Vazquez et al, 2018; Hill et al, 2019; Kiang et al, 2010; Leong et al, 2013; Maldonado et al, 2018; Mayorga et al, 2018; Panchang et al, 2016; Paulus et al, 2019; Perreira et al, 2019; Ramos et al, 2015; Rivera et al, 2015; Rogers-Sirin, 2013; Salgado et al, 2012; Schachter et al, 2012; Torres et al, 2012; Viana et al, 2020; Zvolensky et al, 2016, 2018, 2020). Most of these studies found that increased acculturative stress led to increased depression, anxiety, and psychological stress (Capielo et al, 2015; Castillo et al, 2015; Cervantes et al, 2013, 2019; Corona et al, 2017; Gutierrez-Vazquez et al, 2018; Hill et al, 2019; Kiang et al, 2010; Leong et al, 2013; Maldonado et al, 2018; Mayorga et al, 2018; Muñoz et al, 2019; Paulus et al, 2019; Perreira et al, 2019; Rogers-Sirin, 2013; Torres et al, 2012; Zvolensky et al, 2016, 2018, 2020), while another study indicated that acculturative stress was an indirect effect on anxiety and mood disorders (Bakhshaie et al, 2018).…”
Section: Resultsmentioning
confidence: 99%